Aldose Reductase B1 in Pig Sperm Is Related to Their Function and Fertilizing Ability - Mateo-Otero, Yentel; Ribas-Maynou, Jordi; Delgado-Bermúdez, Ariadna; Llavanera, Marc; Recuero, Sandra; Barranco, Isabel; Yeste, Marc (Frontiers in Endocrinology, 2022)
Aldose reductase B1 (AKR1B1) has been reported to participate in the modulation of male and female reproductive physiology in several mammalian species. In spite of this, whether or not AKR1B1 could be related to sperm quality, functionality and fertilizing ability is yet to be elucidated. The present study, therefore, aimed to investigate: i) the presence of AKR1B1 in epididymal and ejaculated sperm; ii) the relationship between the AKR1B1 present in sperm and the physiology of the male gamete; iii) the liaison between the relative content of AKR1B1 in sperm and their ability to withstand preservation for 72 h; and iv) the potential link between sperm AKR1B1 and in vitro fertility outcomes. Immunoblotting revealed that AKR1B1 is present in both epididymal and ejaculated sperm with a similar relative content. Moreover, the relative levels of AKR1B1 in sperm (36 kDa band) were found to be negatively related to several kinematic parameters and intracellular calcium levels, and positively to the percentage of sperm with distal cytoplasmic droplets after storage. Finally, AKR1B1 amounts in sperm (36 kDa band) were negatively associated to fertilization rate at two days post-fertilization and embryo development at six days post-fertilization. The results of the present work suggest that AKR1B1 in sperm is probably acquired during maturation rather than at ejaculation and could play a role in that process. Moreover, AKR1B1 seems to be related to the sperm resilience to preservation and to their fertilizing capacity, as lower levels of the 36 kDa band (putative inactive form of this protein) result in better reproductive outcomes.